2021
DOI: 10.1002/esp.5113
|View full text |Cite
|
Sign up to set email alerts
|

Influence of physical crust cover on the wind erodibility of soils in the inland Pacific Northwest, USA

Abstract: Soil crusts are especially important for agricultural fields in the inland Pacific Northwest where there is a high wind erosion risk due to exposure of fine erodible soils in fallow croplands. The objective of this study was therefore to evaluate the effect of physical soil crust cover on wind erosion and identify critical soil crust cover amounts to control wind erosion. The effect of crust cover of five loessial soils on wind erosion was tested in a wind tunnel. The results indicated that crust cover appeare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…We observed that the number of erodible particles on farmland increases with wind speed (e.g., 16th to 20th May in 2017 and 20th to 25th April in 2018) and decreases with increasing rainfall (e.g., 4th to 7th May in 2017 and 4th to 16th April in 2018). This has been confirmed in previous literature, whereby the amount of material accumulated each year by wind erosion was closely related to the wind speed and the rainfall amount in a given year (Pierre et al, 2018;de Oro et al, 2019;Pi et al, 2021). The soil particles begin to move when the wind speed is greater than the maximum threshold of frictional velocity between the soil particles and the surface of the farmland (Bergametti et al, 2016).…”
Section: Tillage Treatmentsupporting
confidence: 86%
See 1 more Smart Citation
“…We observed that the number of erodible particles on farmland increases with wind speed (e.g., 16th to 20th May in 2017 and 20th to 25th April in 2018) and decreases with increasing rainfall (e.g., 4th to 7th May in 2017 and 4th to 16th April in 2018). This has been confirmed in previous literature, whereby the amount of material accumulated each year by wind erosion was closely related to the wind speed and the rainfall amount in a given year (Pierre et al, 2018;de Oro et al, 2019;Pi et al, 2021). The soil particles begin to move when the wind speed is greater than the maximum threshold of frictional velocity between the soil particles and the surface of the farmland (Bergametti et al, 2016).…”
Section: Tillage Treatmentsupporting
confidence: 86%
“…Thus, the CT treatment may increase the roughness of the soil surface, changing the airflow field structure and significantly affecting the magnitude and distribution of airflow-soil surface interaction forces (Yang et al, 2020;Carretta et al, 2021). Furthermore, the soil surface layer induced damage as the tillage process may have provided more erodible soil particles for wind erosion, promoting the occurrence of wind erosion on farmland and ultimately influencing the outcome of wind erosion on farmland (Labiadh, 2017;Pi et al, 2021). Thus, tillage treatment is a key anthropogenic influencing factor on wind erosion.…”
Section: Tillage Treatmentmentioning
confidence: 99%
“…The two sandy loam soils have greater inherent wind erosion potential than the three silt loam soils. For example, wind erosion potential is 1405 g m −2 for Warden sandy loam, but on average 495.5 g m −2 across the three silt loam soils (Pi, Webb, et al, 2021). The Palouse, Ritzville, and Walla Walla silt loam soils have higher silt and clay contents and so greater PM10 components potentially available for dust emission than the sandy loam soils (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…The Palouse, Ritzville, and Walla Walla silt loam soils have higher silt and clay contents and so greater PM10 components potentially available for dust emission than the sandy loam soils (Table 1). Previous studies have assessed the relative wind erodibility (Pi, Webb, et al, 2021a; Sharratt et al, 2013; Sharratt & Vaddella, 2012), and threshold friction velocities ( u *t ) of the five soils (Pi, Huggins, & Sharratt, 2020; Pi & Sharratt, 2019), providing a foundation for the research presented here.…”
Section: Methodsmentioning
confidence: 99%
“…Human activities change the ecological environment and often result in intensive soil erosion [7]. The existing studies on soil erosion aggravated by human activities mainly include irrational cultivation [8,9] and overgrazing [10] due to their distinct influences on land, such as roughness reduction [11] and crust destruction [12]. In addition to these human activities, wind erosion is also affected by other rural land uses [13], such as residences and roads, but few studies have been conducted on such subjects.…”
Section: Introductionmentioning
confidence: 99%